Antibacterial and Antioxidant Activities of Adiantum pedatum L. - Karthik M.R, M. Govindappa*; T.S. Sadananda, C.P. Chandrappa, C.B. Shilpashree, (Journal of Phytology, 2011)
The four organic solvent extracts of Adiantum pedatum were tested for the potential antimicrobial activity against clinically important standard reference bacterial strains. The agar disk diffusion method was used to study the antibacterial activity of Adiantum pedatum extracts against 4 bacterial strains Staphylococcus aureus, Klebsiella pneumonia, Pseudomonas aeruginosa and Escherichia coli. The phytochemical screening of extracts was carried out for major phytochemical derivatives in Adiantum pedatum. Two solvent extracts (acetone and ethyl acetate) showed inhibitory activity for Staphylococcus aureus, Klebsiella pneumonia, Pseudomonas aeruginosa and Escherichia coli. The acetone and ethyl acetate extracts were found to be effective against Staphylococcus aureus than Escherichia coli. The phytochemical screening of extracts answered for the major derivative of terpenoids, cardiac glycosides and steroids. The antioxidant activity of the extracts of Adiantum pedatum was determined by the 1, 1-Diphenyl-2-picrylhydrazyl (DPPH), and ferrous reducing antioxidant property (FRAP) methods. Two extracts (acetone and ethyl acetate) showed antibacterial activity against the tested strains Staphylococcus aureus, Klebsiella pneumonia, Pseudomonas aeruginosa and Escherichia coli. Of all, ethanol and hexane extracts did not showed any activity against tested strains. The results also indicate the presence of major phytochemical derivatives in the Adiantum pedatum extracts. Hence, the isolation and purification of therapeutic potential compounds from Adiantum pedatum could be used as an effective source against bacterial diseases in human and plants. The present study provides evidence that the extract of Adiantum pedatum is a potential source of natural antioxidants. Key words: Adiantum pedatum, Phytochemicals, Antibacterial, Antioxidant activity <span style="font-weight: normal; font-size: 7pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-variant: normal! important; mso-fareast-language: EN-SG; mso-font-kerning: 0pt; mso-no-proof: no; mso-ansi-language: EN-SG;" lang="EN-SG">C.P. Chandrappa et al. Antibacterial and Antioxidant Activities of Adiantum pedatum L. J Phytol 3/1 (2011) 26-32.